2022
DOI: 10.1371/journal.pone.0274196
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of homelessness and housing instability and the relationship with mental health disorders among young people transitioning from out-of-home care: Retrospective cohort study using linked administrative data

Abstract: Objectives The study examined the relationship between mental health, homelessness and housing instability among young people aged 15–18 years old who transitioned from out-of-home in 2013 to 2014 in the state of Victoria, Australia with follow-up to 2018. We determined the various mental health disorders and other predictors that were associated with different levels of homelessness risk, including identifying the impact of dual diagnosis of mental health and substance use disorder on homelessness. Methodol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 44 publications
(66 reference statements)
0
6
0
1
Order By: Relevance
“…Previous studies have reported that some youths lack the funds to cover their basic living expenses [19] and feel constricted and breathless [11,15]. Failure to overcome these challenges increases the likelihood of homelessness, which, in turn, increases their risk of developing mental health problems [23]. Therefore, the highest priority for successful independence is practical support that nds a reliable source of income and improves management skills [15].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that some youths lack the funds to cover their basic living expenses [19] and feel constricted and breathless [11,15]. Failure to overcome these challenges increases the likelihood of homelessness, which, in turn, increases their risk of developing mental health problems [23]. Therefore, the highest priority for successful independence is practical support that nds a reliable source of income and improves management skills [15].…”
Section: Discussionmentioning
confidence: 99%
“…Cunningham andDiversi, 2013;Havlicek et al, 2013;Gypen et al, 2017;Munro, 2019;Courtney, 2022. Biehal andWade, 2008;Mendes et al, 2012;Lee et al, 2016. For instance homelessness and mental health issues: Chikwava et al, 2022;Klodnick and Samuels, 2020. And see , Chapter 4.…”
Section: Discussionmentioning
confidence: 99%
“…The dual impact of alcohol misuse and housing insecurity leads to a significant burden on individuals, with acute, social, and chronic consequences [ 28 ]. Hence, housing instability contributes to worsened mental health and substance use [ 29 ]. Interventions to target this at-risk population should improve accessibility to mental health treatment to those with low-income housing in NYC (e.g., affordable, supportive or congregate housing).…”
Section: Discussionmentioning
confidence: 99%